The Complexity of Notarial Law in Indonesia: Application of the Concordance Principle - Satrio Abdillah; Norhasliza Ghapa; Maheran Makhtar (Faculty of Law, Universitas Pekalongan, 2023)
This research aims to examine the urgency of implementing the concordance principle in the complex practice of notarial practice in Indonesia. The research method uses a thematic analysis approach, which is carried out by carefully examining a number of previous research documents and other relevant sources of information. To facilitate in-depth analysis, this study used Nvivo 12 Plus data analysis software. This research reveals that the application of the concordance principle in notarial practice in Indonesia has a significant impact. This principle creates legal certainty, protects public interests, increases efficiency, and supports harmonization with international standards. This also helps prevent legal conflicts, improve notary professionalism, and establish a strong and fair notarial system. By integrating diverse legal sources, the concordance principle maintains the continuity of quality notarial practice in Indonesia while enabling the country to remain in harmony with the demands of the international community in the areas of law and human rights.